C2 2015 3 Edexcel

3

(a)

Since f(x) has remainder 45 when divided by (x +1) we have f(-1) = 45. That is:

f(-1) = 6(-1)^3 + 3(-1)^2 - A + B = -6 + 3 - A + B = 45

So:

B - A - 3 = 45

Giving:

B - A = 48

(b)

Since (2x + 1) is a factor of f(x) we have \displaystyle f\left(-\frac 1 2\right) = 0, so:

\displaystyle 6 \left(-\frac 1 2\right)^3 + 3 \left(-\frac 1 2\right)^2 - \frac 1 2 A + B = 0

So:

\displaystyle B = \frac 1 2 A

Then:

\displaystyle -\frac 1 2 A = 48

So A = -96 and B = -48.

©

We know that f(x) will have the form:

(2x + 1)(3x^2 + ax + b) = 6x^3 + 2ax^2 + 3x^2 + 2bx + ax + b

Comparing coefficients have (2a + 3) = 3, so a = 0, and b = -48, so:

f(x) = (2x + 1)(3x^2 - 48) = 3(2x + 1)(x^2 - 16) = 3(2x+1)(x - 4)(x+4)

1 Like

:hear_no_evil: